AN AMBITION ANALYSIS REPRESENTED BY THE MAIN CHARACTER IN PERFUME: THE STORY OF A MURDERER - Relita Moputi; Dahlia Husain (Universitas Muhammadiyah Gorontalo, 2018)
Literary works are the reflection of real life. Movie is a literary work that tells a story by using some conflict. The character in a movie usually describes the human psychology and behavior. Ambition is one of human psychology. This research discusses about the ambition of the main characters in Perfume: the Story of a Murderer. This movie tells about the ambitious the main character to make a perfume by killed 26 victims. He has an ambition to fulfill their psychogenic needs. The fulfillment of psychogenic needs that is experienced by the main character on the movie is analyzed in Henry Murray's The Need Theory of Personality. This research is conducted by using the qualitative method. This research uses psychological approach to analyze the fictitious of the main character. The result from this study is that the ambition has the causes and the effects.Keywords: Movie, Psychogenic needs, Ambition, Psychological Approach.